ANALYSIS OF NATIONAL AND INTERNATIONAL STANDARDS IN THE FIELD OF PERSONAL ARMOR PROTECTION - BOBROVA, SVITLANA; SERHIENKO, LIUBOV; HALAVSKA, LIUDMYLA; SHATYLO, TETIANA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
With the aim of introducing new domestic standards and specifications and harmonizing them with regulatory documents of the leading countries of the world, an analysis of the main requirements of foreign and existing national standards for means of individual armor protection was carried out and ballistic and other types of tests were carried out to establish the compliance of the protective characteristics of the products with the conditions of use for effective resistance to various types dangers. In world practice, various normative documents are used that regulate the requirements for individual armor protection according to the classification of protection levels, which take into account the characteristics of local weapons, the type of cartridge, the speed of the bullet, the depth measurement of BFS, etc. The work presents the key aspects of the most common regulations of America, Europe and the former CIS countries regarding the methods of testing the main characteristics of body armor of various configurations and purposes. A significant number of tests are required for the acceptance into operation of new armor materials, because the health or life of a person depends on the quality of the finished products. The standards define the general requirements, classes of body armor, their size, the area of ​​the protected area, the procedure for conducting tests for the V50 ballistic limit when determining sparkproof resistance, equipment, test conditions and the classification of levels of protection against small arms, requirements and methods of tests for resistance to a knife attack , resistance to awl or sharpening, as well as ergonomic characteristics, safety requirements and information contained on the body armor. To evaluate the effectiveness of individual armor protection, ballistic tests are conducted using dummies and special installations. The results of the research can be used in designing, production or purchase of means of individual armor protection.